Animal abuse: A close relationship with domestic violence - Gisele Kronhardt Scheffer (Derecho Animal, 2019)
This article aims to address domestic violence and its relation to animal abuse, and to propose alternative solutions. A close relation has been found between domestic violence and animal maltreatment. It is verified that the majority of the aggressors belong to the masculine gender and the most effective way to break the cycle of abuse is education, with the consequent awareness of respect for life in all its forms.